ANALISIS PENGARU KINERJA KEUANGAN TERHADAP PENINGKATAN LABA PADA PT. PEDERAL FINANCE CABANG MAKASSAR - Idham Mannaga (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2013)
This research used time series data from Bank Indonesia’s year’s published financial report of Devisa Bank. After passed the purposive sample phase, the number of valid sample is 20 banks. This research used multiple regression analysis toanalyse the data. F test shows that in simultant variable Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operations Expenses to Operation Income( BOPO) and Loan to Deposit Ratio (LDR), influence Profit Growth. And partially with t test show that Capital Adequacy Ratio (CAR) has significant toward Profit Growth, Non Performing Loan (NPL) has significant toward Return Profit Growth, Operations Expenses to Operation Income ( BOPO) has a significant toward Profit Growth and Loan to deposit Ratio (LDR) has significant toward Profit Growth in Devisa Bank. The result of the research is expected to be a consideration to the company management to manage the company.